2016
DOI: 10.1002/brb3.451
|View full text |Cite
|
Sign up to set email alerts
|

Underestimated associated features in CMT neuropathies: clinical indicators for the causative gene?

Abstract: IntroductionCharcot–Marie–Tooth neuropathy (CMT) is a genetically heterogeneous group of peripheral neuropathies. In addition to the classical clinical phenotype, additional features can occur.MethodsWe studied a wide range of additional features in a cohort of 49 genetically confirmed CMT patients and performed a systematic literature revision.ResultsPatients harbored a PMP22 gene alteration (n = 28) or a mutation in MPZ (n = 11), GJB1 (n = 4), LITAF (n = 2), MFN2 (n = 2), INF2 (n = 1), NEFL (n = 1). We ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 46 publications
0
21
0
1
Order By: Relevance
“…Source . Data from Abe et al (), Agrawal et al (), Baets et al (), Benedetti et al (), Berciano et al (, ), Bhagavati et al (), Butinar et al (), Choi et al (, ), De Jonghe et al (), DiVincenzo et al (), Doppler et al (), Drew et al (), Elbracht et al (), Fabrizi et al (), Fabrizi et al (), Fu and Yuan (), Georgiou et al (), Hashiguchi et al (), Horga et al (), Jordanova et al (), Lerat et al (), Leung et al (), Lin et al (), Luigetti et al (), Manganelli et al (), Mersiyanova et al (), Miltenberger‐Miltenyi et al (), Noto et al (), Pisciotta et al (), Sainio et al (), Shin et al (), Sivera et al (), Werheid et al (), Yang et al (), Yoshihara et al (), Yum et al (), Züchner et al () [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Resultsunclassified
“…Source . Data from Abe et al (), Agrawal et al (), Baets et al (), Benedetti et al (), Berciano et al (, ), Bhagavati et al (), Butinar et al (), Choi et al (, ), De Jonghe et al (), DiVincenzo et al (), Doppler et al (), Drew et al (), Elbracht et al (), Fabrizi et al (), Fabrizi et al (), Fu and Yuan (), Georgiou et al (), Hashiguchi et al (), Horga et al (), Jordanova et al (), Lerat et al (), Leung et al (), Lin et al (), Luigetti et al (), Manganelli et al (), Mersiyanova et al (), Miltenberger‐Miltenyi et al (), Noto et al (), Pisciotta et al (), Sainio et al (), Shin et al (), Sivera et al (), Werheid et al (), Yang et al (), Yoshihara et al (), Yum et al (), Züchner et al () [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Resultsunclassified
“…CMT patients usually present with weakness and atrophy in the feet and then hands, indicating that peripheral neurons with longer axons are more impacted by the disease. However, mutations in a few genes, including GARS1, can cause an upper limb predominance 7,8,47 . This suggests that while axon length is important, additional characteristics contribute to pathogenesis and the spectrum of motor neuron involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Some inf2 mutations appear specific for FSGS or for CMT-FSGS, but others can result in either disease (Fig 5), depending on the individual [Caridi et al, 2014; Jin et al, 2015]. To date, inf2 mutations are the only known genetic cause for cases of CMT accompanied by kidney disease, and these cases can also be accompanied by other phenotypes, including cognitive impairment, deafness, and hand deformities [Werheid et al, 2016]. Considering that CMT symptoms arise before FSGS symptoms [Mademan et al, 2013], it has been suggested that CMT patients be screened for proteinuria (a sign of kidney dysfunction) and, potentially, genotyped for inf2 , as a guide to the appropriate treatment [De Rechter et al, 2015].…”
Section: The Role Of Inf2 In Human Diseasementioning
confidence: 99%